Covid-19 Pandemic and The Healthcare Workers’ Rights and Responsibilities - Khattak, Almas Fasih (International Journal of Pathology, 2022)
Background: The Covid 19 Pandemic has wreaked havoc around the world and continues to do so with changing variants and social dynamics. Millions have died as a result including the frontline healthcare workers (HCWs). We aimed to conduct a survey on the rights and responsibilities of HCWs in their respective healthcare facilities in the wake of COVID-19 pandemic crises. Objectives: The current study was designed to determine the level of satisfaction of healthcare workers with their rights ensured at their respective healthcare facilities they were serving. Methods: A structured questionnaire regarding the rights and responsibilities of HCWs was designed based on World Health Organization’s guidelines to collect data. A 5-point Likert scale was used to rate the individual items on the rights and responsibilities scales. Data was collected through online platform of Google Docs. Completed 547 responses from 26 countries were analysed. SPSS version 24 was used for data entry and analyses. Results: Almost 60% of the participants responded no or that they did not know about their right to compensation, rehabilitation, and curative services in case they were infected with COVID-19. The healthcare workers showed overall lower mean scores for the individual items on the rights scale indicating that they were not satisfied with their rights as healthcare workers at their respective facilities. HCWs showed higher mean scores for the individual items on the responsibilities scale showing that the healthcare workers were aware of and were imparting their duties diligently as healthcare workers in their respective facilities. Conclusion: The findings of the current study indicate that healthcare workers have been found diligent and accountable in imparting their services against the COVID-19 pandemic, however most of them felt deprived of their work rights. Prompt action is needed for provision and assurance of rights of the HCWs as it will bring about a better and effective response against pandemic crises.